Survei Model Sistem Tele-expertise untuk Kasus Dermatologi - Herlambang, Penggalih M; Muhimmah, Izzati (Cermin Dunia Kedokteran, 2019)
Background: Tele-expertise as part of telemedicine can be developed to overcome the problem of uneven distribution of specialist services, especially in dermatology. A technical framework is needed to guide the development of a tele-expertise system to suit the conditions and needs in Indonesia. Methods: The research was carried out in stages, the first stage was needs analysis by survey on general practitioners and dermato-venereologists. The second stage is a literature study and the third stage is the preparation of a tele-expertise framework model. Results and Discussion: In the first phase, 10 general practitioners and 2 skin specialists were willing to fill out the survey. In the second stage, various technical factors were found in telemedicine implementation. A framework model was compiled consisting of 4 main components including workflow, clinical content, infrastructure and interface. Conclusion: A tele-expertise framework model was prepared, especially in the field of dermatology. Further research is needed in the form of prototype testing based on the model for evaluation and development of the framework. In addition, the non-technical approach framework includes ethics, law and draft regulations need to be developed.Latar belakang: Tele-expertise sebagai bagian dari telemedisin dapat dikembangkan untuk mengatasi permasalahan penyebaran layanan dokter spesialis yang belum merata. Untuk itu dibutuhkan kerangka kerja (framework) teknis sebagai panduan pengembangan agar sesuai dengan kondisi dan kebutuhan di Indonesia. Metode: Penelitian bertahap, tahap pertama adalah analisis kebutuhan dengan survei Tahap kedua studi literatur kerangka kerja untuk telemedisin dan tahap ketiga penyusunan model kerangka kerja tele-expertise. Hasil dan Pembahasan: sebuah model framework disusun berdasarkan survei dan literatur yang terdiri dari 4 komponen utama meliputi alur kerja, konten klinis, infrastruktur dan antarmuka. Simpulan: Model kerangka kerja tele-expertise disusun khususnya untuk dermatologi. Diperlukan penelitian lanjut berupa pengujian purwarupa berdasarkan model tersebut untuk evaluasi dan pengembangan kerangka kerja. Selain itu kerangka-kerja pendekatan non-teknis meliputi etika, hukum dan rancangan regulasi perlu dikembangkan.